A Worpitzky boundary theorem for branched continued fractions of the special form - Kuchminska, Kh.Yo. (Carpathian Mathematical Publications, 2016)
For a branched continued fraction of a special form we propose the limit value set for the Worpitzky-like theorem when the element set of the branched continued fraction is replaced by its boundary.